China's Belt and Road Initiative in ASEAN growing presence, recent progress and future challenges - Suthiphand Chirathivat 1953-; Phutthakān Ratchathō̜n; Anupama Devendrakumar (World Scientific, 2022)
"Southeast Asia's interactions with China have tremendously transformed and prospered in the recent decades, with China becoming ever more present on Southeast Asian soil in recent history, touching all dimensions: economic, political, social, and cultural. The current ASEAN-China dynamics are remarkably different from the past, bearing both excitement and caution for watchers. In this context, the advent of China's Belt and Road Initiative (BRI) has added a new perspective to the nature of China's rise in ASEAN. As the various BRI projects continue to unfold in ASEAN countries, public concerns about the impact of these projects are on the rise. However, there has not been enough extensive study on this issue. This edited book contributes towards bridging the knowledge gap by facilitating experts from ASEAN, China, and beyond, to discuss, reflect, debate the ground realities of BRI based on the local governments' and local people's experiences and narratives. The chapters in this volume address various dimensions of the BRI, provide unique perspectives, empirical evidence, and updated information on the overall progress of BRI in ASEAN."
Keywords: ASEAN; Neue Seidenstraße / (DE-627)168241082X / (DE-2867)30234-6; Internationale Wirtschaftsbeziehungen / (DE-627)091368464 / (DE-2867)10617-2; ASEAN-Staaten / (DE-627)091348137 / (DE-2867)17979-3; China / (DE-627)091353777 / (DE-2867)17565-2; Southeast Asia / Foreign economic relations / China; China / Economic policy; China / Foreign economic relations / Southeast Asia; Aufsatzsammlung